Deflecting transmissive light beams with metasurfaces based on crystalline silicon high-contrast grating. (24th December 2018) - Qiu, Yumin; Zhao, Fuwei; Zhu, Xiaoqiang; Li, Juntao; Liang, Haowen; Wang, Jiahui; Cai, Zhigang
Abstract: Dielectric metasurfaces have emerged and expanded rapidly for their success in realizing high-efficiency wavefront control in the optical and infrared ranges. However, devices have either been demonstrated at near-infrared regime using high-index semiconductors such as silicon, or they use lower index dielectric materials such as TiO2 or Si3 N4 and operate in the visible wavelength regime to avoid the optical loss of dielectric materials. It seems that dielectric metasurfaces could not achieve either high index or high device efficiency, simultaneously. Here, we provide a crystalline silicon metasurface scheme to efficiently modulate transmitted light beams at the wavelengths as short as to 532 nm. The unit cell of the metasurfaces consists of high-contrast grating (HCG), which provides full 2 π phase control for circular polarized incident beams in thin film. The demonstration of HCG deflector shows that the device enables high deflecting efficiency as high as those made by transparent materials. Our results provide a paradigm to functionalize transmitted light beams based on crystalline silicon in the visible wavelength regime.